2002
DOI: 10.1097/00126450-200206000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence

Abstract: The contemporary concept of emotional intelligence (EI) as a critical set of management skills is traced through time to its current application for health care administration. EI is defined as proficiencies in intrapersonal and interpersonal skills in the areas of self-awareness, self-regulation, self-motivation, social awareness, and social skills. The contributions of EI to effective management are supported by empirical research in the field. The importance of developing these skills in health care organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…Like those of training and education, the confirmed negative effect of gender on EI in this study is consistent with several studies (e.g., Lopes et al, 2006;Danquah and Wireko, 2014), with some studies reaching a positive effect of gender on EI (Farooq and Ur Rehman, 2011). The fact is that both positive and negative effects of gender on EI represent a significant difference in the EI level of males and females, though no theoretical explanation has been related to this finding.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Like those of training and education, the confirmed negative effect of gender on EI in this study is consistent with several studies (e.g., Lopes et al, 2006;Danquah and Wireko, 2014), with some studies reaching a positive effect of gender on EI (Farooq and Ur Rehman, 2011). The fact is that both positive and negative effects of gender on EI represent a significant difference in the EI level of males and females, though no theoretical explanation has been related to this finding.…”
Section: Discussionsupporting
confidence: 92%
“…More interestingly, a plethora of studies (e.g., Brackett et al, 2004;Danquah and Wireko, 2014;Opuni et al, 2014;Kaur et al, 2015;Tyczkowski et al, 2015;Ozer et al, 2016) have confirmed that EI positively impacts everyday behavior and business performance indicators (e.g., job performance, service quality, customer satisfaction, etc. ), though some studies have not confirmed these effects (Farooq and Ur Rehman, 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is a consensus that higher trait EI is associated with better interpersonal relationships ( Mayer et al, 1999) , academic achievement ( Parker et al, 2004 ; Van Der Zee et al, 2002) and coping ( Salovey et al, 2002) . Trait EI is also considered a fundamental asset for primary leadership and managerial competency in the workplace ( Freshman & Rubino, 2002 ). Managers with higher emotional intelligence skills/competencies may be more successful than their less emotionally intelligent counterparts ( Caruso & Salovey, 2004 ; George, 2000 ), although this assertion may be weakened by the general lack of evidence of how trait EI is related to managerial outcomes ( Murphy, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Managers with higher emotional intelligence skills/competencies may be more successful than their less emotionally intelligent counterparts ( Caruso & Salovey, 2004 ; George, 2000 ), although this assertion may be weakened by the general lack of evidence of how trait EI is related to managerial outcomes ( Murphy, 2006 ). For health care managers, the importance of trait EI as a core competency has been defined as a set of intrapersonal and interpersonal skills in self-awareness, self-regulation, self-motivation, social awareness, and social skills and has been recognized for over a decade ( Freshman & Rubino, 2002 ).…”
Section: Introductionmentioning
confidence: 99%